Traumatic posterior Atlanto-axial dislocation: case report of an atypical C1-C2 dislocation with an anterior arch fracture of C1 - Soufiane Ghailane (BMC Musculoskeletal Disorders, 2019)
Abstract Background An atypical case of a traumatic posterior C1-C2 dislocation with an anterior arch fracture of C1 is reported. A novel conservative treatment for this rare lesion is described. Case presentation An eighty-nine-year-old male fell off a ladder at home and presented with an acute traumatic cervical spine trauma, which we believe involved a distraction mechanism. The patient was neurologically intact; he denied any weakness, numbness or paresthesia. A preoperative CT-scan demonstrated a posterior dislocation with an anterior arch of C1 fracture. Conservative management was elected. Reduction was achieved by closed manual reduction under general anesthesia. A postoperative CT demonstrated a complete reduction of the atlanto-axial dislocation. Conclusion Based on this case report and relevant literature, we present an unusual lesion of the upper cervical spine treated nonoperatively with closed manual reduction under general anesthesia. To date, there is no available consensus for the management of these lesions.